2023
DOI: 10.3390/rs15040975
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Forest Top Height by GEDI: From Sparse Coverage to Continuous Data

Abstract: Estimating consistent large-scale tropical forest height using remote sensing is essential for understanding forest-related carbon cycles. The Global Ecosystem Dynamics Investigation (GEDI) light detection and ranging (LiDAR) instrument employed on the International Space Station has collected unique vegetation structure data since April 2019. Our study shows the potential value of using remote-sensing (RS) data (i.e., optical Sentinel-2, radar Sentinel-1, and radar PALSAR-2) to extrapolate GEDI footprint-leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 77 publications
3
2
0
Order By: Relevance
“…Similar to our results, Ngo et al (2023) also found optical data the most important predictors of RH98 even when radar was included, with a validation R 2 of 0.62 and RMSE of 5 m when compared to an ALS canopy height. All previous studies of scaled-up GEDI RH98 predictions reviewed here had similar biases to those from our study, with under predictions at taller heights and over predictions at lower RH98 values (Healey et al, 2020;Sothe et al, 2022;Ngo et al, 2023).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar to our results, Ngo et al (2023) also found optical data the most important predictors of RH98 even when radar was included, with a validation R 2 of 0.62 and RMSE of 5 m when compared to an ALS canopy height. All previous studies of scaled-up GEDI RH98 predictions reviewed here had similar biases to those from our study, with under predictions at taller heights and over predictions at lower RH98 values (Healey et al, 2020;Sothe et al, 2022;Ngo et al, 2023).…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed promise for applying GEDI-fusion models further back in time than our study period starting in 2016, where we found comparable map validation results for hindcasted years versus years of model creation for all structure metrics. We also found comparable performance for models based on Landsat, topographic, and bioclimatic predictors compared to the model that also incorporated Sentinel-1 and disturbance metrics, which supports the findings of Ngo et al (2023) for the importance of optical data for scaling up GEDI information to continuous extents. The reliance on Landsat data for driving our GEDI-fusion models provides the opportunity to hindcast models further back across the Landsat archive prior to the availability of Sentinel-1 data.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Among the studies focused on scaling up GEDI structure metrics through data fusion approaches, the majority have largely focused upon GEDI canopy heights (Healey et al, 2020;Sothe et al, 2022;Ngo et al, 2023). Similar to these previous studies, we found high accuracies within our maps scaling up RH98 samples to continuous extents through optical and radar-based data fusions with an R 2 of 0.673 and RMSE of 6.996 m when compared against simulated ALS validation samples, and an R 2 of 0.757 and RMSE of 5.445 m when assessed using withheld GEDI footprint testing data.…”
Section: Discussionmentioning
confidence: 99%